Rare earth cobalt permanent magnet, and method and equipment for manufacturing rare earth cobalt permanent magnet

By preparing rare earth cobalt permanent magnets with specific compositions and performing specific heat treatment during sintering and solid solution treatment, 2-17 phases and 1-5 phases are formed, the problem of insufficient magnetic characteristics of rare earth cobalt permanent magnets is solved, and excellent coercivity and rectangularity are achieved.

CN119541980APending Publication Date: 2025-02-28TOKIN CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411177408.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing rare earth cobalt permanent magnets have problems with insufficient coercivity and rectangularity in terms of magnetic properties.

Method used

By preparing a sintered body with a specific composition, including R: 24 to 27 wt%, Fe: 23 to 27 wt%, Cu: 4.0 to 5.0 wt%, Zr: 1.5 to 2.5 wt%, Mn: 0.1 to 2.5 wt%, and rapid cooling and aging treatment were performed during sintering and solution treatment, a rare earth cobalt permanent magnet with a 2-17 phase of Th2Zn17 type structure and a 1-5 phase of RCo5 type structure were formed.

Benefits of technology

The excellent magnetic properties of rare earth cobalt permanent magnets have been achieved, especially in terms of coercive force and rectangularity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119541980A_ABST
    Figure CN119541980A_ABST
Patent Text Reader

Abstract

A rare earth cobalt permanent magnet according to one aspect of the present disclosure includes a sintered body having a composition of R: 24 to 27 wt% (R is a sum of rare earth elements including at least Sm), Fe: 23 to 27 wt%, Cu: 4.0 to 5.0 wt%, Zr: 1.5 to 2.5 wt%, Mn: 0.1 to 2.5 wt%, and Co and unavoidable impurities as a remainder, in which the rare earth cobalt permanent magnet includes a plurality of crystal grains and a grain boundary phase; the average concentration of Mn in the grain boundary phase is 0.5 to 1.5 times higher than the average concentration of Mn in the grains; the crystal grain comprises a 2-17 phase with a Th2Zn17 type structure and a 1-5 phase with an RCo5 type structure; and the average concentration of Mn in the 1-5 phases is 0.4 to 1.5 times higher than the average concentration of Mn in the 2-17 phases.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This disclosure claims priority to and the benefit of Japanese Patent Application No. 2013-140900, filed in the Japan Patent Office on August 31, 2023, the entire contents of which are hereby incorporated by reference into this application. Technical Field

[0003] The invention relates to a rare earth cobalt permanent magnet, and a method and equipment for manufacturing the rare earth cobalt permanent magnet. Background Art

[0004] As a type of permanent magnet, rare earth cobalt permanent magnets such as samarium-cobalt magnets are known. Regarding rare earth cobalt permanent magnets, research on rare earth cobalt permanent magnets containing Fe, Cu, Zr, etc. has been conducted from various aspects, for example, to improve their magnetic properties.

[0005] For example, Japanese Unexamined Patent Application Publication No. 2017-168827 discloses a permanent magnet comprising specific corresponding amounts of rare earth elements Fe, Cu, Co, Zr, Ti, and Hf, and having a Th2Zn-containing 17 The structure of the crystal grains composed of the main phase of the type crystalline phase and the grain boundaries between the crystal grains, wherein the average grain size of the crystal grains is 50 to 100 μm.

[0006] International Patent Publication No. WO2015 / 140829 discloses a specific permanent magnet, which contains specific corresponding amounts of rare earth elements Fe, Cu, Co, Zr, Ti and Hf, and has a Th2Zn 17 A unit cell phase of a type crystal phase and a Cu-rich phase having a Cu concentration higher than that of the unit cell phase, wherein an average diameter of the unit cell phase is less than 220 nm.

[0007] Further, Japanese Unexamined Patent Application Publication No. 2020-188140 discloses a rare earth cobalt permanent magnet comprising specific corresponding amounts of rare earth elements R, Fe, Cu, Co and Zr, and having a Th2Zn-containing 17 type crystal phase and a cell wall of a crystal phase having an RCo5 type structure surrounding the cell phase, wherein the concentration of the rare earth element in the cell wall is at least 25at% higher than the concentration of the rare earth element in the cell phase. Summary of the invention

[0008] An object of the present disclosure is to provide a rare earth cobalt permanent magnet having excellent magnetic properties, in particular excellent coercive force and excellent squareness, and to provide a method and an apparatus for manufacturing such a rare earth cobalt permanent magnet.

[0009] The rare earth cobalt permanent magnet according to an aspect of the present disclosure includes a sintered body having the following composition: R: 24 to 27 wt% (R is the sum of rare earth elements including at least Sm), Fe: 23 to 27 wt%, Cu: 4.0 to 5.0 wt%, Zr: 1.5 to 2.5 wt%, Mn: 0.1 to 2.5 wt%, and the balance includes Co and inevitable impurities, wherein the rare earth cobalt permanent magnet includes a plurality of crystal grains and a grain boundary phase, and the average concentration of Mn in the grain boundary phase is 0.5 to 1.5 times higher than the average concentration of Mn in the crystal grains, and the crystal grains include a 2-17 phase having a Th2Zn 17 type structure and a 1-5 phase having an RCo5 type structure, and the average concentration of Mn in the 1-5 phase is 0.4 to 1.5 times higher than the average concentration of Mn in the 2-17 phase.

[0010] The device according to an aspect of the present disclosure is a device including the above rare earth cobalt permanent magnet.

[0011] The method for manufacturing a rare earth cobalt permanent magnet according to an aspect of the present disclosure includes: a step (I) of preparing an ingot containing raw materials such that the ingot has the following composition after sintering: R: 24 to 27 wt% (R is the sum of rare earth elements including at least Sm), Fe: 23 to 27 wt%, Cu: 4.0 to 5.0 wt%, Zr: 1.5% to 2.5 wt%, Mn: 0.1 to 2.5 wt%, and the balance includes Co and inevitable impurities; a pulverizing step (II) of pulverizing the ingot into powder; a pressure molding step (III) of molding the powder into a molded body; a sintering step (IV) of heating the molded body to form a sintered body; a solution treatment step (V) of heating the sintered body to perform solution treatment; and a rapid cooling step (VI) of rapidly cooling the sintered body after the solution treatment step (V), and an aging treatment step (VII) of forming a 2-17 phase having a Th2Zn 17 type structure and a 1-5 phase having an RCo5 type structure. The step (I) of preparing the ingot includes: a first ingot heat treatment step of treating a mixture of raw materials at a first ingot heat treatment temperature; and a second ingot heat treatment step of treating the mixture at a second ingot heat treatment temperature after the first ingot heat treatment step. When S1 represents the sintering temperature of the molded body and S2 represents the temperature of the solution treatment, the first ingot heat treatment temperature T1 satisfies the relationship S1 - 50 ≤ T1 ≤ S1 (however, when the temperature difference between S1 and S2 is equal to or less than 50 °C, the first ingot heat treatment temperature T1 satisfies the relationship S2 < T1 ≤ S1), and the second ingot heat treatment temperature T2 satisfies the relationship S2 - 30 ≤ T2 ≤ S2.

[0012] According to the present disclosure, it is possible to provide a rare earth cobalt permanent magnet having excellent magnetic properties, particularly excellent coercive force and excellent rectangularity, and to provide a method and an apparatus for manufacturing such a rare earth cobalt permanent magnet.

[0013] The above and other objects, features and advantages of the present disclosure will be more fully understood from the detailed description and accompanying drawings given below, which are given in an illustrative manner and thus are not to be construed as limiting the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is a schematic diagram showing an example of a cross section of a rare earth cobalt permanent magnet according to an embodiment;

[0015] Figure 2 for Figure 1 An enlarged schematic diagram of part A (part of a grain) shown in FIG.

[0016] Figure 3 is an electron micrograph of a rare earth cobalt permanent magnet according to an embodiment;

[0017] Figure 4 is a diagram showing the analysis results of the composition of the rare earth cobalt permanent magnet according to the embodiment;

[0018] Figure 5 is an electron micrograph of a rare earth cobalt permanent magnet according to an embodiment; and

[0019] Figure 6 : is a graph showing the analysis results of the composition of the rare earth cobalt permanent magnet according to the embodiment. DETAILED DESCRIPTION

[0020] Embodiments according to the present disclosure will be described below.

[0021] It should be noted that, unless otherwise specified, a numerical range such as “nm” or “n to m” (ie, “from n to m”) includes a lower limit value and an upper limit value.

[0022] <Rare earth cobalt permanent magnet>

[0023] A rare earth cobalt permanent magnet (hereinafter also referred to as a permanent magnet) according to the present embodiment includes a sintered body having the following composition: R: 24 to 27 wt% (R is the sum of rare earth elements including at least Sm), Fe: 23 to 27 wt%, Cu: 4.0 to 5.0 wt%, Zr: 1.5 to 2.5 wt%, Mn: 0.1 to 2.5 wt%, and Co and unavoidable impurities as the balance, wherein the rare earth cobalt permanent magnet includes a plurality of crystal grains and a grain boundary phase, and the average concentration of Mn in the grain boundary phase is 0.5 to 1.5 times higher than the average concentration of Mn in the crystal grains, and the crystal grains include Th2Zn17 The 2-17 phase has a RCo5 type structure and the 1-5 phase has an RCo5 type structure, and the average concentration of Mn in the 1-5 phase is 0.4 to 1.5 times higher than that in the 2-17 phase.

[0024] In the present embodiment, the term "rare earth element R" is a general term for Sc, Y and lanthanide elements (elements with atomic numbers of 57 to 71), and includes at least Sm as a rare earth element R. As the rare earth element R, only Sm can be used, or a combination of Sm and at least one type of other rare earth elements can be used. As with other rare earth elements, Pr, Nd, Ce and La are preferred in view of magnetic properties. Further, in view of magnetic properties, based on the total amount of rare earth element R, the content of Sm is preferably 80wt% or more, more preferably 90wt% or more, and even more preferably 95wt% or more. The permanent magnet contains 24wt% to 27wt%, preferably 24wt% to 26wt% of the rare earth element R. By making the permanent magnet contain the rare earth elements in the above ratio, a permanent magnet with high magnetic anisotropy and high coercive force can be obtained.

[0025] The permanent magnet contains 23wt% to 27wt%, preferably 23wt% to 26.5wt% of Fe. By containing more than 23wt% of Fe, the saturation magnetization is improved. Further, by adjusting the Fe content to less than 27wt%, the permanent magnet has a higher coercive force.

[0026] The permanent magnet contains 4.0 wt% to 5.0 wt%, preferably 4.0 wt% to 4.7 wt% of Cu. By containing 4.0 wt% or more of Cu, the permanent magnet has a higher coercive force. Further, by adjusting the Cu content to 5.0 wt% or less, magnetization degradation is suppressed.

[0027] The permanent magnet contains 0.1wt% to 2.5wt%, preferably 0.15wt% to 1.5wt% of Mn. By containing more than 0.1wt% of Mn, the concentration of Cu in the grain boundary phase can be increased. Further, by making the permanent magnet contain Mn within the above range, a crystal structure containing grains with relatively large and uniform grain size can be easily obtained, thereby improving the squareness ratio. On the other hand, when the Mn content exceeds 2.5wt%, the grain size tends to become smaller rather than larger.

[0028] It is presumed that the melting point is lowered by including 0.1 wt% or more of Mn, so that more liquid phase appears during sintering and a concentration distribution of Cu, etc. is formed. Further, it is presumed that the grain size of the grains increases due to the large amount of liquid phase. Further, it is presumed that Mn also contributes to the non-magnetization of the grain boundary phase, so that the appearance of the reverse magnetic domain in the grain boundary phase is suppressed.

[0029] The permanent magnet contains 1.5 wt% to 2.5 wt%, preferably 1.9 wt% to 2.3 wt% Zr. By containing 1.5 wt% to 2.5% Zr, a permanent magnet having a high maximum energy product (BH)m can be obtained, which is the maximum magnetostatic energy that the magnet can hold.

[0030] Further, the balance of the permanent magnet includes Co and inevitable impurities. By making the permanent magnet contain Co, the thermal stability of the permanent magnet is improved. However, when the content of Co is too large, the content of Fe is relatively reduced. Inevitable impurities refer to elements that are inevitably mixed in the permanent magnet from raw materials or during the manufacturing process. Examples of inevitable impurities include but are not limited to C, N, P, S, Al, Ti, Cr, Ni, Hf, Sn and W. In the permanent magnet, based on the total amount of the permanent magnet, the total ratio of inevitable impurities is preferably 5wt% or less, more preferably 1wt% or less, and even more preferably 0.1wt% or less. For example, it is possible to measure the content ratio of each of the elements contained in a local area (i.e., a small area) of the permanent magnet by using energy dispersive X-ray spectroscopy (EDX: Energy dispersive X-ray spectrometry).

[0031] Will refer to Figure 1 and Figure 2 The metallographic structure of the permanent magnet according to the present disclosure is described. Figure 1 is a schematic diagram showing an example of a cross section of a permanent magnet according to the present embodiment, and Figure 2 yes Figure 1 FIG. 1 is an enlarged schematic diagram of portion A (a portion of grain 10) shown in FIG. Figure 1 As shown in the example shown in FIG. 1 , the rare earth cobalt permanent magnet 100 according to the present embodiment includes a plurality of crystal grains 10 and a grain boundary phase 20 existing between the crystals 10. Further, as Figure 2 As shown in the example shown in FIG. 1 , each crystal grain 10 has the following structure (hereinafter also referred to as a unit cell structure), that is, including Th2Zn 17 The crystal grain 10 includes a phase 11 having a TbCu type structure (hereinafter also referred to as a 2-17 phase 11) and a phase 12 having an RCo5 type structure (hereinafter also referred to as a 1-5 phase 12), wherein the 2-17 phase is a main phase (having a volume ratio of 50% or more). Note that the crystal grain 10 may further include a crystal phase (not shown) having a TbCu7 type structure (hereinafter also referred to as a 1-7 phase).

[0032] With Th2Zn 17Phase 11 of the RCo5 type structure is a crystal structure with an R-3m type space group. In permanent magnets, generally speaking, the Th portion is occupied by rare earth elements and Zr, and the Zn portion is occupied by Co, Cu, Fe and Zr. Further, in phase 12 with an RCo5 type structure, generally, the R portion is occupied by rare earth elements and Zr, and the Co portion is occupied by Co, Cu and Fe. Further, in a crystalline phase with a TbCu7 type structure, generally, the Tb portion is occupied by rare earth elements and Zr, and the Cu portion is occupied by Co, Cu and Fe. The crystal structure can be determined by an X-ray diffraction method.

[0033] As described above, in the permanent magnet according to the present disclosure, the average concentration of Mn in the grain boundary phase 20 is 0.5 to 1.5 times higher than the average concentration of Mn in the grains 10. Further, the average concentration of Mn in the 1-5 phase 12 is 0.4 to 1.5 times higher than the average concentration of Mn in the 2-17 phase 11. Therefore, a rare earth cobalt permanent magnet having excellent magnetic properties, particularly excellent coercive force and excellent rectangularity can be obtained.

[0034] In the permanent magnet, the average concentration of Mn in the grain boundary phase 20 is preferably 0.8 to 1.2 times higher than the average concentration of Mn in the grains 10. Further, the average concentration of Cu and Zr in the grain boundary phase 20 may be at least twice higher than the average concentration of Cu and Zr in the grains 10, and preferably at least four times higher. Further, the average concentration of Mn in the 1-5 phase 12 is 0.8 to 1.0 times higher than the average concentration of Mn in the 2-17 phase 11. In the present embodiment, by adjusting the various values ​​so that they fall within their respective ranges, a rare earth cobalt permanent magnet having more excellent magnetic properties can be obtained.

[0035] Figure 3 is an electron micrograph of the rare earth cobalt permanent magnet according to the present embodiment, and shows the crystal grains 10 and the grain boundary phase 20 . Figure 4 1 is a diagram showing the analysis results of the composition of the rare earth cobalt permanent magnet according to the present embodiment, and is a diagram showing the analysis results of the composition near the crystal grains 10 and the grain boundary phase 20. That is, Figure 4 The graph shown in is the result of analyzing the composition in a region starting from a grain 10 , passing through a grain boundary phase 20 , and ending at another grain 10 .

[0036] like Figure 3 As shown in the electron micrograph shown in FIG. , the grain boundary phase 20 exists between the grains 10. Further, as Figure 4As shown in the analysis results of the composition shown in , the composition of the various elements in the grain boundary phase 20 varies more than that in the grain 10. Specifically, the amount of Fe and Co in the grain boundary phase 20 is reduced and the amount of Cu and Zr is increased compared to the amount in the grain 10. Further, in the present embodiment, the average concentration of Cu and Zr in the grain boundary phase 20 is preferably at least twice as high as the average concentration of Cu and Zr in the grain 10, and more preferably at least four times as high. Further, the average concentration of Mn in the grain boundary phase 20 is preferably 0.5 to 1.5 times higher than the average concentration of Mn in the grain 10, and more preferably 0.8 to 1.2 times higher. That is, in the present embodiment, Mn is uniformly dispersed in the grains 10 and the grain boundary phase 20 compared to Cu and Zr.

[0037] Figure 5 1 is an electron micrograph of the rare earth cobalt permanent magnet according to the present embodiment, and shows the 2-17 phase 11 and the 1-5 phase 12 in the grains. Figure 6 1 is a diagram showing the analysis results of the composition of the rare earth cobalt permanent magnet according to the present embodiment, and is a diagram showing the analysis results of the composition of the 2-17 phase 11 and the 1-5 phase 12. That is, Figure 6 The graph shown in is a result of analyzing the composition in a region starting from a 2-17 phase 11 , passing through a 1-5 phase 12 , and ending with another 2-17 phase 11 .

[0038] like Figure 5 As shown in the electron micrograph shown in FIG, there are 2-17 phases 11 and 1-5 phases 12 in the grains. Figure 6 As shown in the analysis results of the composition shown in , the composition of various elements in the 1-5 phase 12 varies more than that in the 2-17 phase 11. Specifically, the amount of Fe, Co and Zr in the 1-5 phase 12 is reduced and the amount of Cu and Sm is increased compared to the amount in the 2-17 phase 11. Further, in the present embodiment, the average concentration of Mn in the 1-5 phase 12 is preferably 0.4 to 1.5 times higher than the average concentration of Mn in the 2-17 phase 11, more preferably 0.8 to 1.0 times higher. That is, in the present embodiment, Mn is uniformly dispersed in the grains compared to Cu and Zr. That is, Mn is uniformly dispersed in the 2-17 phase 11 and the 1-5 phase 12 compared to Cu and Zr.

[0039] In the present embodiment, the "average concentration" of each element is the arithmetic mean concentration at the points where the analysis of each phase is performed.

[0040] Note that Figures 3 to 6The results of electron micrographs and composition analysis are shown in , which can be measured by the following method. First, the sample is physically polished with waterproof polishing paper or the like. Thereafter, the surface is processed using a focused ion beam (FIB: Focused Ion Beam) or ion milling so that irregularities are not formed on it. For the sample processed as described above, the target point is observed by using a transmission electron microscope (TEM: Transmission Electron Microscope). In this process, the magnification for the grain boundary phase is 3,000 to 5,000, and the magnification for the unit cell structure in the grain is 10,000 to 30,000. Further, the composition is directly analyzed at the observation point by using energy dispersive X-ray spectroscopy (EDX: Energy Dispersive X-ray Spectroscopy). The composition is preferably analyzed at 5 to 20 nm in the grain boundary phase and at 0.5 to 2.0 nm in the unit cell structure.

[0041] According to the present disclosure, the density of the sintered body for permanent magnet is preferably 8.20 to 8.45 g / cm 3 , and more preferably 8.25 to 8.40 g / cm 3 In particular, by adjusting the density of the sintered body so as to fall within the above range, the residual magnetic flux density (Br) and the squareness ratio can be improved.

[0042] One of the characteristics of the permanent magnet according to the present disclosure is to homogenize its structure through heat treatment such as sintering / solution treatment and subsequent rapid cooling, and to develop the characteristics of the permanent magnet by further performing aging treatment.

[0043] The residual magnetic flux density (Br) of the permanent magnet according to the present disclosure is 11.8 kG or more, preferably 12.0 kG or more. Further, the coercive force (Hcj) is 20 kOe or more, preferably 22 kOe or more. Further, the maximum energy product (BH)m is 260 kJ / m 3 Above, preferably 265 kJ / m 3 Note that the maximum energy product (BH)m is the maximum magnetostatic energy that a magnetic material can maintain, and represents the maximum value of the product of the magnetic flux density B and the magnetic field H for the BH demagnetization curve in the second quadrant (demagnetization curve) of the magnetization curve (BH curve).

[0044] The squareness ratio of the permanent magnet represented by the ratio (Hk / Hcj) of the magnetic field (Hk) to the coercive force (Hcj) is 65% or more, preferably 70% or more. Note that regarding the magnetic field (Hk), the magnetic field at which 90% of the residual magnetization is magnetized is represented by Hk.

[0045] It is assumed that in the permanent magnet according to the present disclosure, coercive force is generated because the magnetic domain wall is pinned between two phases (i.e., the 2-17 phase and the 1-5 phase) when the magnetic domain wall moves. Further, since Fe and Cu are concentrated in the 2-17 phase and the 1-5 phase respectively when separated into two phases, the squareness ratio is improved and the maximum energy product (BH)m is increased. Further, the more constant the composition ratio between the 2-17 phase and the 1-5 phase is throughout the sample, the more excellent the obtained magnetic properties are.

[0046] To measure the magnetic properties, first, the sample is processed into a predetermined shape. In the case of using a DC (direct current) B-H tracer, the magnet is magnetized by applying a magnetic field about three to four times higher than the predicted Hcj, and then the measurement is performed according to the usage method of the device. In the case of using a pulse-type B-H tracer, magnetization is not required.

[0047] <Method for manufacturing a rare earth cobalt permanent magnet>

[0048] Next, a method for manufacturing a rare earth cobalt permanent magnet according to an embodiment will be described.

[0049] The method for manufacturing a rare earth cobalt permanent magnet according to an aspect of the present disclosure includes: a step (I) of preparing an ingot containing raw materials such that the ingot has the following composition after sintering: R: 24 to 27 wt% (R is the sum of rare earth elements including at least Sm), Fe: 23 to 27 wt%, Cu: 4.0 to 5.0 wt%, Zr: 1.5 to 2.5 wt%, Mn: 0.1 to 2.5 wt%, and the balance including Co and inevitable impurities; a pulverizing step (II) of pulverizing the ingot into powder; a pressure molding step (III) of molding the powder into a molded body; a sintering step (IV) of heating the molded body to form a sintered body; a solution treatment step (V) of heating the sintered body to perform solution treatment; and a rapid cooling step (VI) of rapidly cooling the sintered body after the solution treatment step (V), and an aging treatment step (VII) of forming a 2-17 phase having a Th2Zn 17 type structure and a 1-5 phase having an RCo5 type structure. The step (I) of preparing the ingot includes: a first ingot heat treatment step of treating a mixture of raw materials at a first ingot heat treatment temperature; and a second ingot heat treatment step of treating the mixture at a second ingot heat treatment temperature after the first ingot heat treatment step. When S1 represents the sintering temperature of the molded body and S2 represents the temperature of the solution treatment, the first ingot heat treatment temperature T1 satisfies the relationship S1 - 50 ≤ T1 ≤ S1 (however, when the temperature difference between S1 and S2 is equal to or less than 50 °C, the first ingot heat treatment temperature T1 satisfies the relationship S2 < T1 ≤ S1), and the second ingot heat treatment temperature T2 satisfies the relationship S2 - 30 ≤ T2 ≤ S2.

[0050] A method for manufacturing a permanent magnet according to the present disclosure will be described in detail below.

[0051] In the step (I) of preparing an ingot including raw materials, Sm is used as a base element as a raw material. Further, rare earth elements such as Nd, Pr and Ce; Fe, Cu and Co; and a base alloy such as FeZr or CuZr are used. Note that it is preferable to select a base alloy including a composition having a low eutectic temperature because this makes it easy to homogenize the composition of the alloy ingot. For example, FeZr or CuZr is preferred. In the case of FeZr, a weight ratio of about 80% Fe and about 20% Zr is suitable for the present embodiment, and in the case of CuZr, a weight ratio of about 50% Cu and about 50% Zr is suitable for the present embodiment. The raw materials are mixed so as to obtain a predetermined composition, put the mixture into a crucible (such as an alumina crucible), and melted by a high-frequency melting furnace at 1×10 -2 The alloy ingot is obtained by dissolving the mixture in a vacuum below 1 torr or in an inert gas atmosphere and casting the molten metal into a mold.

[0052] Considering the manufacturing cost, it is desirable if the obtained alloy is used as it is. However, in the present embodiment, heat treatment is performed to make the structure more uniform and thereby improve the magnetic properties. Specifically, in order to eliminate and homogenize the phases that have been formed during casting, a first ingot heat treatment step performed at a first ingot heat treatment temperature and a second ingot heat treatment step performed at a second ingot heat treatment temperature are performed.

[0053] In the first ingot heat treatment step, in order to suppress the evaporation of Sm, the first ingot heat treatment temperature is preferably lower than the sintering temperature and 50 °C higher than the solution treatment temperature. However, when the difference between the sintering temperature and the solution treatment temperature is equal to or less than 50 °C, the first ingot heat treatment temperature is preferably lower than the sintering temperature and higher than the solution treatment temperature. Specifically, when the sintering temperature of the green body is denoted as S1 and the solution treatment temperature (solution treatment temperature) is denoted as S2, the first ingot heat treatment temperature T1 is preferably set so as to satisfy the relationship S1 - 50 ≤ T1 ≤ S1 (however, when the temperature difference between S1 and S2 is equal to or less than 50 °C, the first ingot heat treatment temperature T1 satisfies the relationship S2 < T1 ≤ S1). Further, in the present embodiment, the first ingot heat treatment temperature T1 is more preferably set so as to satisfy S1 - 30 ≤ T1 ≤ S1 (however, when the temperature difference between S1 and S2 is equal to or less than 30 °C, the first ingot heat treatment temperature T1 satisfies the relationship S2 < T1 ≤ S1). The heat treatment time of the first ingot heat treatment step is preferably 0.5 to 3 hours, and more preferably 1 to 2 hours. By setting the heat treatment temperature and the heat treatment time to fall within the above ranges, the dendritic phase and other undesirable phases can be eliminated while suppressing the evaporation of Sm.

[0054] Further, in the second ingot heat treatment step, in order to improve the homogenization effect, the second ingot heat treatment temperature is preferably equal to or lower than the solution treatment temperature and higher than the temperature 30 degrees lower than the solution treatment temperature. Specifically, the second ingot heat treatment temperature T2 is preferably set so as to satisfy the relationship S2 - 30 ≤ T2 ≤ S2. Further, in the present embodiment, more preferably, the second ingot heat treatment temperature T2 is set so as to satisfy the relationship S2 - 20 ≤ T2 ≤ S2. The heat treatment time of the second ingot heat treatment step is preferably 1 to 10 hours, and more preferably 3 to 8 hours. By setting the heat treatment time to fall within the above ranges, the structure can be made uniform while suppressing the evaporation of Sm.

[0055] When changing the temperature from the first ingot heat treatment temperature T1 to the second ingot heat treatment temperature T2, in order to suppress the evaporation of Sm and improve the homogenization effect, it is preferable to decrease the temperature at a rate of 0.1 to 20 °C / min, and more preferably at a rate of 1 to 10 °C / min. Note that in the present embodiment, the ingot heat treatment step is not limited to two steps. That is, the ingot heat treatment step can be divided into three or more steps. Further, instead of casting the molten metal into a mold, a method called strip casting can be used in which a sheet-like alloy piece having a thickness of about 1 mm is obtained by dropping the molten metal onto a copper roll.

[0056] Next, the ingot prepared as described above is crushed into powder (crushing step (II)). First, a powder having an average size of about 100 to 500 μm is obtained by coarsely crushing the ingot. Then, a powder having an average size of about 1 to 10 μm is obtained by finely crushing the coarsely crushed powder with a ball mill or a jet mill. By obtaining a powder having such an average particle size, the sintering time of the sintering step (which will be described later) can be reduced, and a uniform permanent magnet can be manufactured. Further, in the present embodiment, in order to improve the sintering performance, the finely ground powder preferably has the following particle size distribution, namely, D10 (the particle size value of less than 10% of the whole powder) is less than 4 μm; the median diameter D50 (the particle size value of less than 50% of the whole powder) is 5 to 8 μm; and D90 (the particle size value of less than 90% of the whole powder) is less than 16 μm. Further, more preferably, the finely ground powder preferably has the following particle size distribution, that is, D10 is less than 3 μm; D50 is 5 to 7 μm; and D90 is less than 15 μm. By adopting the above particle size distribution, a powder having a density of 8.20 g / cm 3 The above sintered bodies.

[0057] Next, a molded body is manufactured by press-molding the powder obtained as described above (press-molding step (III)). In the present embodiment, the obtained powder is preferably press-molded in a constant magnetic field to make the crystal orientation of the powder consistent, thereby improving its magnetic properties. There are no particular restrictions on the relationship between the direction of the magnetic field and the direction of pressurization, and they can be appropriately selected according to the shape of the product, etc. For example, when manufacturing an annular magnet or a thin plate-shaped magnet, a parallel magnetic field pressurization in which a magnetic field is applied in a direction parallel to the pressurization direction can be used. On the other hand, in order to obtain excellent magnetic properties, it is preferred to use a right-angle magnetic field pressurization in which a magnetic field is applied at right angles to the pressurization direction.

[0058] The magnitude of the magnetic field is not limited to any particular value, and depending on the purpose of the product, the magnetic field may be, for example, a magnetic field of 15 kOe or less, or a magnetic field of 15 kOe or more. However, in order to obtain excellent magnetic properties, it is preferred to perform press molding in a magnetic field of 15 kOe or more. In addition, the pressure in press molding may be appropriately adjusted according to the size, shape, etc. of the product. For example, the pressure may be 0.5 to 2.0 tons / cm 2 .

[0059] Next, a sintered body is obtained by heating the molded body obtained as described above (sintering step (IV)). In the present embodiment, as long as the obtained sintered body is sufficiently densified, the conditions for sintering can be arbitrarily determined. For example, known conditions can be used. In order to densify the sintered body, the sintering temperature is preferably 1,170°C to 1,215°C, more preferably 1,180°C to 1,210°C. By adjusting the temperature to below 1,215°C, the evaporation of rare earth elements (especially Sm) can be prevented, thereby enabling the manufacture of permanent magnets with excellent magnetic properties. In addition, in the present embodiment, since the melting point tends to be lowered due to the inclusion of Mn, sintering can be sufficiently performed at a temperature below 1215°C.

[0060] Regarding the temperature increase conditions during the sintering step, in order to remove the adsorbed gas contained in the molded body, it is preferred to start the vacuum treatment at room temperature and increase the temperature at a rate of 1 to 10°C / min. During the temperature increase process, a hydrogen atmosphere may be used instead of performing the vacuum treatment. Even in this case, it is preferred to convert the hydrogen atmosphere into a vacuum atmosphere within a temperature range of 1150°C or less. The sintering time is preferably 20 to 210 minutes, and more preferably 30 to 150 minutes, so as to fully densify the sintered body while preventing Sm from evaporating. In addition, in order to prevent oxidation, the above-mentioned sintering step is preferably carried out in a vacuum of 1,000 Pa or less or in an inert gas atmosphere. In addition, in order to increase the density of the sintered body, it is more preferred to perform the sintering step in a vacuum of 100 Pa or less.

[0061] Next, a solution treatment is performed by heating the sintered body (solution treatment step (V)). The solution treatment is a step for forming a 1-7 phase (TbCu7 type structure), which is a precursor for separation into a 2-17 phase and a 1-5 phase. From the production process point of view, the solution treatment is performed in a continuous manner, rather than cooling the sintered body to room temperature after sintering. Note that when the temperature changes from the sintering temperature to the solution treatment temperature, in order to suppress the evaporation of Sm and improve the homogenization effect, the temperature is preferably reduced at a rate of 0.1 to 10°C / min, and more preferably at a rate of 0.2 to 2.5°C / min. The solution treatment is performed at a vacuum of 1,000 Pa or less at 1,110°C to 1,165°C or in an inert atmosphere. Since the optimal solution treatment temperature varies depending on the composition, it is preferred to perform the solution treatment at a temperature suitable for the composition. If the solution treatment temperature is too high, homogenization cannot be performed due to residual liquid phase, and if the solution treatment temperature is too low, homogenization requires a long time. Therefore, it is preferred to perform solution treatment at 1,120 to 1,160°C. Further, the solution treatment time is preferably 5 to 150 hours, and more preferably 10 to 100 hours. If the solution treatment time is too short, homogenization of the 1-7 phase becomes insufficient, and if the solution treatment time is too long, Sm evaporates and thus excellent magnetic properties cannot be obtained. Therefore, the solution treatment time is preferably within the above range.

[0062] Next, the sintered body is rapidly cooled after solution treatment (rapid cooling step (VI)). Rapid cooling is a process for maintaining the 1-7 phases obtained in solution treatment, and if rapid cooling is insufficient, the structure changes during cooling. In particular, the temperature range necessary for rapid cooling to be effective is a range from the solution treatment temperature to 600°C. In order to maintain the 1-7 phases, rapid cooling is required at a rate of 60°C / min or more within the above range, and preferably at a rate of 80°C / min or more.

[0063] Next, the 2-17 phase and the 1-5 phase are formed by performing an aging treatment on the molded body that has undergone the rapid cooling step (aging treatment step (VII)). Although the aging treatment temperature is not limited to any specific temperature, in order to obtain a permanent magnet with the 2-17 phase as the main phase and homogeneously (or uniformly) containing the 2-17 phase and the 1-5 phase, it is preferred to use a method in which the molded body is maintained at a temperature of 700 to 900°C for 2 to 20 hours, and then the cooling rate is set to 2°C / min or less until the molded body is cooled to below 400°C. By maintaining the molded body at a temperature of 700°C to 900°C for 2 to 20 hours, the 2-17 phase and the 1-5 phase can be uniformly formed. Specifically, the aging treatment is preferably carried out in a temperature range of 800 to 850°C. Further, in order to obtain satisfactory magnetic properties, the cooling rate is preferably adjusted to below 2°C / min, and more preferably below 0.5°C / min.

[0064] By using the method for manufacturing a rare earth cobalt permanent magnet according to the above-mentioned embodiment, a rare earth cobalt permanent magnet having the above-mentioned characteristics can be manufactured. That is, a rare earth cobalt permanent magnet comprising a plurality of grains and a grain boundary phase can be manufactured, wherein: the average concentration of Mn in the grain boundary phase is 0.5 to 1.5 times the average concentration of Mn in the grains; the grains include Th2Zn 17 type structure and a 1-5 phase having an RCo5 type structure; and the average concentration of Mn in the 1-5 phase is 0.4 to 1.5 times higher than the average concentration of Mn in the 2-17 phase.

[0065] <Device>

[0066] According to the embodiment of the present disclosure, it is also possible to provide a device including the above-mentioned rare earth cobalt permanent magnet. Examples of such devices include clocks (watches), electric motors, various instruments, communication equipment, computer terminals, speakers, video disks and sensors. Further, since the magnetic force of the rare earth cobalt permanent magnet according to the present embodiment is unlikely to deteriorate even at high ambient temperatures due to its excellent heat resistance, it can also be suitable for use in, for example, angle sensors or ignition coils used in the engine room of a car, or drive motors for hybrid electric vehicles (HEV: Hybrid electric vehicle), etc. Specifically, as described above, since the rare earth cobalt permanent magnet according to the present embodiment has a high residual magnetic flux density, a high coercive force and a high rectangular ratio, it can be suitable for use in a variable magnetic field motor, thereby making it possible to obtain a variable magnetic field motor that achieves high efficiency in a range from low speed to high speed.

[0067] According to the present embodiment described above, it is possible to provide a rare earth cobalt permanent magnet having excellent magnetic characteristics, particularly excellent coercive force and excellent rectangularity, and to provide a method and an apparatus for producing such a rare earth cobalt permanent magnet.

[0068] [Example]

[0069] Hereinafter, the present disclosure will be described in a specific manner by using Examples and Comparative Examples. Note that the present disclosure is not limited to the following description of Examples and the like.

[0070] (Examples 1 to 3)

[0071] A base alloy and various raw materials each containing 20% ​​Fe and 80% Zr were prepared (i.e., mixed) to obtain the compositions of Examples 1 to 3 as shown in Table 1-1. Then, they were dissolved with a high-frequency melting furnace, and the molten metal was cast into an alloy ingot. The obtained alloy ingot was heat treated at 1,155°C (Example 1), 1,180°C (Example 2), or 1,205°C (Example 3) for two hours, and then heat treated at 1,125°C for five hours. Then, the heat-treated alloy ingot was coarsely crushed into particles having an average size of about 100 to 500 μm in an inert gas, and then finely crushed by using a ball mill in an inert gas so that: D10 becomes about 2.5 μm; D50 becomes about 6 μm; and D90 becomes about 13.5 μm. By heating the alloy ingot at 1 ton / cm in a magnetic field of 15 kOe, the resulting mixture was subjected to a pulverization process. 2 The powders are pressed at a pressure of 1000 to obtain a compact.

[0072] The molded body is sintered at 1205°C for one hour under a vacuum of less than 1,000 Pa, and then solution treated at 1130°C for 30 hours. Then, the molded body is rapidly cooled from 1,000°C to 600°C at a cooling rate of 80°C / min. After rapid cooling, the molded body is kept at 825°C for 25 hours, and then aging treatment is performed under the condition that the molded body is slowly cooled to 350°C at a cooling rate of 0.5°C / min. Through these processes, a permanent magnet is obtained. Note that in Table 1-1, ΔT1 is the difference between the sintering temperature (S1) and the first ingot heat treatment temperature (T1), and ΔT2 is the difference between the solution treatment temperature (S2) and the second ingot heat treatment temperature (T2). Further, S1-S2 is the difference between the sintering temperature (S1) and the solution treatment temperature (S2). The same applies to other tables.

[0073] The magnetic properties of the permanent magnets were measured and preserved as molded bodies. The magnetic properties of the permanent magnets were measured by using a BH tracer. Further, the permanent magnets were subjected to necessary processes, and the microstructure was observed and the composition was analyzed by using TEM / EDX. Table 1-2 shows the residual flux density (Br), coercive force (Hcj), rectangular ratio (Hk / Hcj), the ratio of the grain boundary phase with an average concentration of Mn to the grain with an average concentration of Mn, the ratio of the 1-5 phase to the 2-17 phase in the grain (unit cell structure) with an average concentration of Mn, the ratio of the grain boundary phase with an average concentration of Cu to the grain with an average concentration of Cu, and the ratio of the grain boundary phase with an average concentration of Zr to the grain with an average concentration of Zr for each permanent magnet.

[0074] (Comparative Examples 1 and 2)

[0075] Permanent magnets according to Comparative Examples 1 and 2 were obtained in the same manner as in Examples 1 to 3, except that the first ingot heat treatment temperature (T1) was changed to the temperatures shown in Comparative Examples 1 and 2 in Table 1-1.

[0076] [Table 1-1]

[0077]

[0078] [Table 1-2]

[0079]

[0080] As shown in Tables 1-1 and 1-2, in Examples 1 to 3, the average concentration of Mn in the grain boundary phase is 0.5 to 1.5 times the average concentration of Mn in the grains. Further, in Examples 1 to 3, the average concentration of Mn in phases 1-5 is 0.4 to 1.2 times the average concentration of Mn in phases 2-17. Further, in Examples 1 to 3, the average concentration of Cu and Zr in the grain boundary phase is at least twice higher than the average concentration of Cu and Zr in the grains. Therefore, in Examples 1 to 3, the residual magnetic flux density (Br), coercive force (Hcj), and rectangular ratio (Hk / Hcj) have excellent values.

[0081] (Examples 4 to 6)

[0082] A base alloy and various raw materials each containing 20% ​​Fe and 80% Zr were prepared (i.e., mixed) to obtain the compositions of Examples 4 to 6 as shown in Table 2-1. Then, they were dissolved with a high-frequency melting furnace, and the molten metal was cast into an alloy ingot. The obtained alloy ingot was heat treated at 1,170°C for one hour, and then heat treated at 1,110°C (Example 4), 1,125°C (Example 5), or 1,140°C (Example 6) for five hours. Then, the heat-treated alloy ingot was coarsely crushed into particles having an average size of about 100 to 500 μm in an inert gas, and then finely crushed by using a ball mill in an inert gas so that: D10 becomes about 2.5 μm; D50 becomes about 6 μm; and D90 becomes about 13.5 μm. By heating the alloy ingot at 1 ton / cm in a magnetic field of 15 kOe, the resulting mixture was subjected to a pulverization process. 2 The powders are pressed at a pressure of 1000 to obtain a compact.

[0083] The molded body was sintered at 1,200°C for 1.5 hours under a vacuum of less than 1,000 Pa, and then solution treated at 1,140°C for 100 hours. Then, the molded body was rapidly cooled from 1,000°C to 600°C at a cooling rate of 80°C / min. After rapid cooling, the molded body was held at 825°C for 25 hours, and then aging treated under the condition that the molded body was slowly cooled to 350°C at a cooling rate of 0.5°C / min. Through these processes, a permanent magnet was obtained.

[0084] The magnetic properties of the permanent magnets were measured and preserved as molded bodies. The magnetic properties of the permanent magnets were measured by using a BH tracer. Further, the permanent magnets were subjected to necessary processes, and the microstructure was observed and the composition was analyzed by using TEM / EDX. Table 2-2 shows the residual flux density (Br), coercive force (Hcj), rectangular ratio (Hk / Hcj), the ratio of the grain boundary phase with an average concentration of Mn to the grain with an average concentration of Mn, the ratio of the 1-5 phase to the 2-17 phase in the grain (unit cell structure) with an average concentration of Mn, the ratio of the grain boundary phase with an average concentration of Cu to the grain with an average concentration of Cu, and the ratio of the grain boundary phase with an average concentration of Zr to the grain with an average concentration of Zr for each permanent magnet.

[0085] (Comparative Examples 3 to 4)

[0086] Permanent magnets according to Comparative Examples 3 and 4 were obtained in the same manner as Examples 4 to 6, except that the second ingot heat treatment temperature (T2) was changed to the temperature shown in Comparative Examples 3 and 4 in Table 2-1.

[0087] [Table 2-1]

[0088]

[0089] [Table 2-2]

[0090]

[0091] As shown in Tables 2-1 and 2-2, in Examples 4 to 6, the average concentration of Mn in the grain boundary phase is 0.5 to 0.9 times the average concentration of Mn in the grains. In addition, in Examples 4 to 6, the average concentration of Mn in Phases 1-5 is 0.6 to 0.8 times the average concentration of Mn in Phases 2-17. In addition, in Examples 4 to 6, the average concentration of Cu and Zr in the grain boundary phase is at least twice higher than the average concentration of Cu and Zr in the grains. Therefore, in Examples 4 to 6, the residual magnetic flux density (Br), coercive force (Hcj), and squareness ratio (Hk / Hcj) have excellent values.

[0092] (Examples 7 to 12)

[0093] A base alloy and various raw materials each containing 20% ​​Fe and 80% Zr were prepared (ie, mixed) to obtain the compositions of Examples 7 to 12 as shown in Table 3-1. Then, they were dissolved with a high-frequency melting furnace, and the molten metal was cast into an alloy ingot. In Example 7, the alloy ingot obtained was heat treated at 1,170°C for one hour, and then at 1,135°C for six hours. In Example 8, the alloy ingot obtained was heat treated at 1,170°C for one hour, and then at 1,130°C for six hours. In Example 9, the alloy ingot obtained was heat treated at 1,185°C for one hour, and then at 1,135°C for six hours. In Example 10, the alloy ingot obtained was heat treated at 1185°C for one hour, and then at 1130°C for six hours. In Example 11, the alloy ingot obtained was heat treated at 1210°C for one hour, and then at 1135°C for six hours. In Example 12, the obtained alloy ingot was heat-treated at 1210° C. for one hour, and then heat-treated at 1130° C. for six hours.

[0094] Then, the heat-treated alloy ingot was coarsely pulverized into particles having an average size of about 100 to 500 μm in an inert gas, and then finely pulverized by using a ball mill in an inert gas so that: D10 becomes about 2.5 μm; D50 becomes about 6 μm; and D90 becomes about 13.5 μm. 2 The powders are pressed at a pressure of 1000 rpm to obtain a compact.

[0095] In Examples 7, 9 and 11, the molded body was sintered at 1,210°C for 0.5 hours under a vacuum of less than 1,000 Pa, and then solution treated at 1,165°C for 50 hours. In Examples 8, 10 and 12, the molded body was sintered at 1,210°C for 0.5 hours under a vacuum of less than 1,000 Pa, and then solution treated at 1,160°C for 50 hours. Then, the molded body was rapidly cooled from 1,000°C to 600°C at a cooling rate of 80°C / min. After rapid cooling, the molded body was kept at 825°C for 25 hours, and then aging treatment was performed under the condition that the molded body was slowly cooled to 350°C at a cooling rate of 0.5°C / min. Through these processes, permanent magnets were obtained.

[0096] The magnetic properties of the permanent magnets were measured and preserved as molded bodies. The magnetic properties of the permanent magnets were measured by using a BH tracer. Further, the permanent magnets were subjected to necessary processes, and the microstructure was observed and the composition was analyzed by using TEM / EDX. Table 3-2 shows the residual flux density (Br), coercive force (Hcj), rectangular ratio (Hk / Hcj), the ratio of the grain boundary phase with an average concentration of Mn to the grains with an average concentration of Mn, the ratio of the 1-5 phase to the 2-17 phase in the grains (unit cell structure) with an average concentration of Mn, the ratio of the grain boundary phase with an average concentration of Cu to the grains with an average concentration of Cu, and the ratio of the grain boundary phase with an average concentration of Zr to the grains with an average concentration of Zr for each permanent magnet.

[0097] (Comparative Examples 5 to 8)

[0098] Permanent magnets according to Comparative Examples 5 to 8 were obtained in the same manner as in Examples 7 to 12, except that the conditions of heat treatment, sintering and solution treatment of the alloy ingots were changed as follows.

[0099] In Comparative Example 5, the obtained alloy ingot was heat-treated at 1,160°C for one hour, and then at 1,135°C for six hours. In Comparative Example 6, the obtained alloy ingot was heat-treated at 1,160°C for one hour, and then at 1,130°C for six hours. In Comparative Example 7, the obtained alloy ingot was heat-treated at 1,215°C for one hour, and then at 1,135°C for six hours. In Comparative Example 8, the obtained alloy ingot was heat-treated at 1,215°C for one hour, and then at 1,130°C for six hours.

[0100] Further, in Comparative Examples 5 and 7, the molded bodies were sintered at 1,210° C. for one hour in a vacuum of less than 1,000 Pa, and then solution treated at 1,165° C. for six hours. In Comparative Examples 6 and 8, the molded bodies were sintered at 1,210° C. for one hour in a vacuum of less than 1,000 Pa, and then solution treated at 1,160° C. for six hours.

[0101] [Table 3-1]

[0102]

[0103] [Table 3-2]

[0104]

[0105] As shown in Table 3-1 and Table 3-2, in Examples 7 to 12, the average concentration of Mn in the grain boundary phase is 0.5 to 0.8 times the average concentration of Mn in the grains. In addition, in Examples 7 to 12, the average concentration of Mn in phases 1-5 is 0.4 to 0.8 times the average concentration of Mn in phases 2-17. Further, in Examples 7 to 12, the average concentration of Cu and Zr in the grain boundary phase is at least twice as high as the average concentration of Cu and Zr in the grains. Therefore, in Examples 7 to 12, the residual magnetic flux density (Br), coercive force (Hcj) and rectangular ratio (Hk / Hcj) have excellent values.

[0106] (Examples 13 to 20)

[0107] A base alloy and various raw materials each containing 20% ​​Fe and 80% Zr were prepared (ie, mixed) to obtain the compositions of Examples 13 to 20 as shown in Table 4-1. Then, they were dissolved with a high-frequency melting furnace, and the molten metal was cast into an alloy ingot. In Example 13, the alloy ingot obtained was heat treated at 1,185°C for one hour, and then at 1,130°C for six hours. In Example 14, the alloy ingot obtained was heat treated at 1,160°C for one hour, and then at 1,100°C for ten hours. In Examples 15 and 16, the alloy ingot obtained was heat treated at 1,180°C for two hours, and then at 1,120°C for eight hours. In Examples 17 and 18, the alloy ingot obtained was heat treated at 1,175°C for three hours, and then at 1,125°C for four hours. In Examples 19 and 20, the obtained alloy ingots were heat treated at 1,195°C for 1.5 hours and then at 1,115°C for nine hours.

[0108] Then, the heat-treated alloy ingot was coarsely pulverized into particles having an average size of about 100 to 500 μm in an inert gas, and then finely pulverized by using a ball mill in an inert gas so that: D10 becomes about 2.5 μm; D50 becomes about 6 μm; and D90 becomes about 13.5 μm. 2 The powders are pressed at a pressure of 1000 rpm to obtain a compact.

[0109] In Example 13, the molded body was sintered at 1,215°C for 1.5 hours under a vacuum of less than 1,000 Pa, and then solution treated at 1,140°C for 30 hours. In Example 14, the molded body was sintered at 1,170°C for 2.5 hours under a vacuum of less than 1,000 Pa, and then solution treated at 1,110°C for 40 hours. In Examples 15 and 16, the molded body was sintered at 1,185°C for 2.0 hours under a vacuum of less than 1,000 Pa, and then solution treated at 1,125°C for 50 hours. In Examples 17 and 18, the molded body was sintered at 1,195°C for 1.0 hour under a vacuum of less than 1,000 Pa, and then solution treated at 1,140°C for 60 hours. In Examples 19 and 20, the molded bodies were sintered at 1,200° C. for 1.0 hour under a vacuum of less than 1,000 Pa, and then solution treated at 1,130° C. for 50 hours.

[0110] Then, the molded body was rapidly cooled from 1,000° C. to 600° C. at a cooling rate of 80° C. / min. After rapid cooling, the molded body was held at 825° C. for 25 hours, and then aging treatment was performed under the condition that the molded body was slowly cooled to 350° C. at a cooling rate of 0.5° C. / min. Through these processes, a permanent magnet was obtained.

[0111] The magnetic properties of the permanent magnets were measured and preserved as molded bodies. The magnetic properties of the permanent magnets were measured by using a BH tracer. Further, the permanent magnets were subjected to necessary processes, and the microstructure was observed and the composition was analyzed by using TEM / EDX. Table 4-2 shows the residual flux density (Br), coercive force (Hcj), rectangular ratio (Hk / Hcj), the ratio of the grain boundary phase with an average concentration of Mn to the grains with an average concentration of Mn, the ratio of the 1-5 phase to the 2-17 phase in the grains (unit cell structure) with an average concentration of Mn, the ratio of the grain boundary phase with an average concentration of Cu to the grains with an average concentration of Cu, and the ratio of the grain boundary phase with an average concentration of Zr to the grains with an average concentration of Zr for each permanent magnet.

[0112] (Comparative Examples 9 to 18)

[0113] A base alloy and various raw materials each containing 20% ​​Fe and 80% Zr were prepared (ie, mixed) to obtain the compositions of Examples 9 to 18 as shown in Table 4-1. Then, they were dissolved with a high-frequency melting furnace, and the molten metal was cast into an alloy ingot. In Comparative Examples 9 and 10, the alloy ingots obtained were heat treated at 1,185°C for one hour, and then at 1,130°C for six hours. In Comparative Examples 11 and 12, the alloy ingots obtained were heat treated at 1,160°C for one hour, and then at 1,100°C for 10 hours. In Comparative Examples 13 and 14, the alloy ingots obtained were heat treated at 1,180°C for two hours, and then at 1,120°C for eight hours. In Comparative Examples 15 and 16, the alloy ingots obtained were heat treated at 1,175°C for three hours, and then at 1,125°C for four hours. In Comparative Examples 17 and 18, the obtained alloy ingots were heat-treated at 1,195° C. for 1.5 hours, and then heat-treated at 1,115° C. for nine hours.

[0114] Then, the heat-treated alloy ingot was coarsely pulverized into particles having an average size of about 100 to 500 μm in an inert gas, and then finely pulverized by using a ball mill in an inert gas so that: D10 becomes about 2.5 μm; D50 becomes about 6 μm; and D90 becomes about 13.5 μm. 2 The powders are pressed at a pressure of 1000 rpm to obtain a compact.

[0115] In Comparative Examples 9 and 10, the molded bodies were sintered at 1,215°C for 1.5 hours under a vacuum of less than 1,000 Pa, and then solution treated at 1,140°C for 30 hours. In Comparative Examples 11 and 12, the molded bodies were sintered at 1,170°C for 2.5 hours under a vacuum of less than 1,000 Pa, and then solution treated at 1,110°C for 40 hours. In Comparative Examples 13 and 14, the molded bodies were sintered at 1,185°C for 2.0 hours under a vacuum of less than 1,000 Pa, and then solution treated at 1,125°C for 50 hours. In Comparative Examples 15 and 16, the molded bodies were sintered at 1,195°C for 1.0 hour under a vacuum of less than 1,000 Pa, and then solution treated at 1,140°C for 60 hours. In Comparative Examples 17 and 18, the molded bodies were sintered at 1,200° C. for 1.0 hour under a vacuum of less than 1,000 Pa, and then solution treated at 1,130° C. for 50 hours.

[0116] Then, the molded body was rapidly cooled from 1,000° C. to 600° C. at a cooling rate of 80° C. / min. After rapid cooling, the molded body was held at 825° C. for 25 hours, and then aging treatment was performed under the condition that the molded body was slowly cooled to 350° C. at a cooling rate of 0.5° C. / min. Through these processes, a permanent magnet was obtained.

[0117] The magnetic properties of the permanent magnets were measured and preserved as molded bodies. The magnetic properties of the permanent magnets were measured by using a BH tracer. Further, the permanent magnets were subjected to necessary processes, and the microstructure was observed and the composition was analyzed by using TEM / EDX. Table 3-2 shows the residual flux density (Br), coercive force (Hcj), rectangular ratio (Hk / Hcj), the ratio of the grain boundary phase with an average concentration of Mn to the grains with an average concentration of Mn, the ratio of the 1-5 phase to the 2-17 phase in the grains (unit cell structure) with an average concentration of Mn, the ratio of the grain boundary phase with an average concentration of Cu to the grains with an average concentration of Cu, and the ratio of the grain boundary phase with an average concentration of Zr to the grains with an average concentration of Zr for each permanent magnet.

[0118] [Table 4-1]

[0119]

[0120] [Table 4-2]

[0121]

[0122] As shown in Table 4-1 and Table 4-2, the composition of Sm as a rare earth element is changed in Example 13 and Comparative Examples 9 and 10. Based on the results of Example 13 and Comparative Examples 9 and 10, when the composition range of Sm is 24 to 27wt%, the residual magnetic flux density (Br), coercive force (Hcj) and rectangular ratio (Hk / Hcj) have excellent values. In Example 14 and Comparative Examples 11 and 12, the composition of Fe is changed. Based on the results of Example 14 and Comparative Examples 11 and 12, when the composition range of Fe is 23 to 27wt%, the residual magnetic flux density (Br), coercive force (Hcj) and rectangular ratio (Hk / Hcj) have excellent values. In Examples 15 and 16 and Comparative Examples 13 and 14, the composition of Cu is changed. Based on the results of Examples 15 and 16, and Comparative Examples 13 and 14, when the composition of Cu is 4.0 to 5.0 wt %, the residual magnetic flux density (Br), the coercive force (Hcj), and the squareness ratio (Hk / Hcj) have excellent values.

[0123] In Examples 17 and 18 and Comparative Examples 15 and 16, the composition of Zr was changed. Based on the results of Examples 17 and 18 and Comparative Examples 15 and 16, when the composition of Zr was 1.5 to 2.5 wt%, the residual magnetic flux density (Br), the coercive force (Hcj), and the rectangular ratio (Hk / Hcj) had excellent values. In Examples 19 and 20 and Comparative Examples 17 and 18, the composition of Mn was changed. Based on the results of Examples 19 and 20 and Comparative Examples 17 and 18, when the composition of Zr was 0.1 to 2.5 wt%, the residual magnetic flux density (Br), the coercive force (Hcj), and the rectangular ratio (Hk / Hcj) had excellent values.

[0124] As shown in the above-mentioned Examples 1 to 20, when the samples are manufactured under predetermined conditions, the average concentration of Mn in the grain boundary phase is in the range of 0.5 to 1.5 times the average concentration of Mn in the grains (Condition A). Further, the average concentration of Mn in the 1-5 phases is 0.4 to 1.5 times the average concentration of Mn in the 2-17 phases (Condition B). Further, the average concentration of Cu and Zr in the grain boundary phases is at least twice the average concentration of Cu and Zr in the grains (Condition C). In addition, the residual magnetic flux density (Br) is above 11.8 kG, the coercive force (Hcj) is 20 kOe, and the rectangular ratio (HK / Hcj) is above 65%.

[0125] On the other hand, in the samples where the heat treatment conditions of the ingots are out of the predetermined range or the composition is out of the predetermined range (i.e., in Comparative Examples 1 to 18), at least one or all of the above conditions A to C are not satisfied. In addition, in Comparative Examples 1 to 18, at least one or all of the following conditions are not satisfied: the residual magnetic flux density (Br) is 11.8 kG or more; the coercive force (Hcj) is 20 kOe; and the squareness ratio (HK / Hcj) is 65% or more.

[0126] From the disclosure thus described, it will be apparent that the embodiments of the present disclosure may be varied in many ways. These variations should not be regarded as a departure from the spirit and scope of the present disclosure, and all such modifications obvious to those skilled in the art are intended to be included within the scope of the following claims.

Claims

1. A rare earth cobalt permanent magnet, comprising a sintered body having the following composition: R: 24 to 27 wt%, wherein: R is the total of rare earth elements including at least Sm; Fe: 23 to 27 wt%; Cu: 4.0 to 5.0 wt%; Zr: 1.5 to 2.5 wt%; Mn: 0.1 to 2.5 wt%; and Co and inevitable impurities are included as the balance, wherein the rare earth cobalt permanent magnet includes a plurality of crystal grains and a grain boundary phase, and the average concentration of Mn in the grain boundary phase is 0.5 to 1.5 times higher than the average concentration of Mn in the crystal grains, and The grains include Th2Zn 17 The 2-17 phase has a RCo5 type structure and the 1-5 phase has an RCo5 type structure, and the average concentration of Mn in the 1-5 phase is 0.4 to 1.5 times higher than the average concentration of Mn in the 2-17 phase.

2. The rare earth cobalt permanent magnet according to claim 1, wherein: the average concentrations of Cu and Zr in the grain boundary phase are at least twice higher than the average concentrations of Cu and Zr in the crystal grains.

3. The rare earth cobalt permanent magnet according to claim 1 or 2, wherein: The average concentration of Mn in the grain boundary phase is 0.8 to 1.2 times higher than the average concentration of Mn in the crystal grains.

4. The rare earth cobalt permanent magnet according to claim 1 or 2, wherein: The average concentration of Mn in the 1-5 phase is 0.8 to 1.0 times higher than the average concentration of Mn in the 2-17 phase.

5. The rare earth cobalt permanent magnet according to claim 1 or 2, wherein: The average concentrations of Cu and Zr in the grain boundary phase are at least four times higher than the average concentrations of Cu and Zr in the crystal grains.

6. The rare earth cobalt permanent magnet according to claim 1 or 2, wherein: The remanent flux density Br is 11.8 kG or more.

7. The rare earth cobalt permanent magnet according to claim 1 or 2, wherein: The coercivity Hcj is 20 kOe or more.

8. The rare earth cobalt permanent magnet according to claim 1 or 2, wherein: The rectangular ratio as the ratio Hk / Hcj of the magnetic field Hk to the coercivity Hcj is 65% or more.

9. An apparatus, the apparatus comprising the rare earth cobalt permanent magnet according to claim 1 or 2.

10. A method for manufacturing a rare earth cobalt permanent magnet, the method comprising: a step (I) of preparing an ingot containing raw materials such that the ingot has the following composition after sintering: R: 24 to 27 wt%, wherein R is the total of rare earth elements including at least Sm; Fe: 23 to 27 wt%; Cu: 4.0 to 5.0 wt%; Zr: 1.5 to 2.5 wt%; Mn: 0.1 to 2.5 wt%; and Co and inevitable impurities are included as the balance; a crushing step (II) of crushing the ingot into powder; a pressure molding step (III) of molding the powder into a molded body; a sintering step (IV) of heating the molded body to form a sintered body; a solution treatment step (V) of heating the sintered body to perform solution treatment; and a rapid cooling step (VI) of rapidly cooling the sintered body after the solution treatment step (V), and Formation of Th2Zn 17 The aging treatment step (VII) of the 2-17 phases having the RCo5 type structure and the 1-5 phases having the RCo5 type structure, wherein the step (I) of preparing the ingot includes: a first ingot heat treatment step of treating the mixture of the raw materials at a first ingot heat treatment temperature; and a second ingot heat treatment step of treating the mixture at a second ingot heat treatment temperature after the first ingot heat treatment step, and when S1 represents the sintering temperature of the molded body and S2 represents the temperature of the solution treatment, the first ingot heat treatment temperature T1 satisfies the relationship S1 - 50 ≤ T1 ≤ S1, wherein when the temperature difference between S1 and S2 is equal to or less than 50 °C, the first ingot heat treatment temperature T1 satisfies the relationship S2 < T1 ≤ S1, and the second ingot heat treatment temperature T2 satisfies the relationship S2 - 30 ≤ T2 ≤ S2.

11. The method for manufacturing a rare earth cobalt permanent magnet according to claim 10, wherein The heat treatment time of the first ingot heat treatment step is not less than 0.5 hours and not more than 3.0 hours, and The heat treatment time of the second ingot heat treatment step is not less than 1.0 hour and not more than 10.0 hours.

12. The method for producing a rare earth cobalt permanent magnet according to claim 10 or 11, wherein The sintering step (IV) is a step of heating the molded body at a temperature of not less than 1,170° C. and not more than 1,215° C. for not less than 20 minutes and not more than 210 minutes, The solution treatment step (V) is a step of heating the sintered body at a temperature of not less than 1110° C. and not more than 1165° C. for not less than 5 hours and not more than 150 hours, and The rapid cooling step (VI) is a step of cooling the sintered body from the solution treatment temperature to 600° C. by cooling at a cooling rate of 60° C. / min or more for at least a period of time after the solution treatment step (V).

13. The method for producing a rare earth cobalt permanent magnet according to claim 10 or 11, wherein: In the pulverizing step (II), the ingot is pulverized so that a particle size D10 of the ingot becomes smaller than 4 μm; a particle size D50 becomes not smaller than 5 μm and not larger than 8 μm; and a particle size D90 becomes smaller than 16 μm.

14. The method for producing a rare earth cobalt permanent magnet according to claim 10 or 11, wherein The rare earth cobalt permanent magnet comprises a plurality of crystal grains and a grain boundary phase, and an average concentration of Mn in the grain boundary phase is 0.5 to 1.5 times higher than an average concentration of Mn in the crystal grains, and The grains include Th2Zn 17 The 2-17 phase has a RCo5 type structure and the 1-5 phase has an RCo5 type structure, and the average concentration of Mn in the 1-5 phase is 0.4 to 1.5 times higher than the average concentration of Mn in the 2-17 phase.

Citation Information

Patent Citations

  • Quantum dot structure body and formation method of the same, wavelength conversion element, photo-photo converter, and photoelectric conversion device

    JP2013140900A

  • Permanent magnet, motor, and generator

    WO2015140829A1